Los mandatos de la práctica del rugby en las expresiones subjetivas de una joven universitaria (2017)
This research provides a new panorama for the approach of the sport and the athletes, taking into account the historical development that the social sciences and their different branches had investigated about the sport, especially the sports psychology. Whith this point of view, it was analyzed the way in which the mandates of the practice of rugby are reflected in the subjective expressions of a young university student in the city of Cali. In addition, it is intended to identify, through the discourse of the young person, the interpretation of the mandates stipulated by the sport which include values and norms of conduct. In the same way, there is interest in knowing the concept of gender identity that is built on the young woman, taking into account that this sport is governed by ideologies of masculinity. A qualitative methodology was used, with methodological tool as the life stories and discourse analysis.